2018
DOI: 10.1002/dys.1605
|View full text |Cite
|
Sign up to set email alerts
|

Resolving reading disability—Childhood predictors and adult‐age outcomes

Abstract: We examined frequency of adult‐age reading disability (RD) and its childhood predictors among 48 adults (20 to 39 years) with documented childhood RD, and contrasted their cognitive skills, education, and employment with 37 matched controls. Among individuals with childhood RD, more than half had improved in their reading fluency to the level where the set criterion for adult‐age RD was not met anymore. More fluent rapid naming, less severe childhood RD, and multiple support providers in childhood together pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 58 publications
4
31
0
Order By: Relevance
“…PA forms the basis for the initial stages of literacy learning especially (de Jong & van der Leij, 2003; Papadopoulos, Spanoudis, & Georgiou, 2016), whereas other abilities, for example RAN, contribute to literacy learning throughout development (Manis, Seidenberg, & Doi, 1999; Torgesen, Wagner, Rashotte, Burgess, & Hecht, 1997; Wimmer, 1993). Research into resolving dyslexia has shown that adults with resolved childhood dyslexia display PA performance that is comparable to that of adults with unresolved dyslexia, whereas RAN performance of resolvers resembles that of typical readers (Eloranta, Närhi, Eklund, Ahonen, & Aro, 2018). These findings indicate that while poor PA may hamper literacy development in early stages especially, later problems may occur and remain as a result of deficiencies in other abilities such as RAN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PA forms the basis for the initial stages of literacy learning especially (de Jong & van der Leij, 2003; Papadopoulos, Spanoudis, & Georgiou, 2016), whereas other abilities, for example RAN, contribute to literacy learning throughout development (Manis, Seidenberg, & Doi, 1999; Torgesen, Wagner, Rashotte, Burgess, & Hecht, 1997; Wimmer, 1993). Research into resolving dyslexia has shown that adults with resolved childhood dyslexia display PA performance that is comparable to that of adults with unresolved dyslexia, whereas RAN performance of resolvers resembles that of typical readers (Eloranta, Närhi, Eklund, Ahonen, & Aro, 2018). These findings indicate that while poor PA may hamper literacy development in early stages especially, later problems may occur and remain as a result of deficiencies in other abilities such as RAN.…”
Section: Discussionmentioning
confidence: 99%
“…The second issue concerns the difference in remediation opportunity between the groups. Early identified students undergo early intervention programs and/or remedial teaching in order to improve reading skills (e.g., Ehrhardt, Huntington, Molino, & Barbaresi, 2013; Eloranta et al, 2018; Tijms, 2011). In contrast, late identified students are less likely to have been offered intervention programs at that time.…”
Section: Discussionmentioning
confidence: 99%
“…Given this letter-sound consistency, in transparent orthographies DD is mainly characterized by slow, although accurate reading (Wimmer, 1993; Coltheart and Leahy, 1996; Zoccolotti et al, 1999; Ziegler and Goswami, 2005; Martens and de Jong, 2006). This pattern of difficulties seems to persist in adulthood (Martin et al, 2010; Lindgrén and Laine, 2011; Re et al, 2011; Suárez-Coalla and Cuetos, 2015; Eloranta et al, 2018).…”
Section: Introductionmentioning
confidence: 95%
“…Developmental dyslexia (DD) is a specific learning disorder characterized by problems with accurate or fluent word recognition, poor letter decoding, and poor spelling abilities, that affects up to 15% of the population worldwide (American Psychiatric Association [APS], 2013). Although most of the research regarding DD has been conducted with children, reading difficulties persist throughout life (Bruck, 1985; Finucci et al, 1985; Nergård-Nilssen and Hulme, 2014; Shrewsbury, 2016; Eloranta et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Persistent difficulties in reading do not only affect child's performance in classroom but may also lead to lower educational attainment and higher risk for unemployment in adulthood (Eloranta, Närhi, Eklund, Ahonen, & Aro, 2019). Therefore, interventions for prevention of reading difficulties and their negative consequences are of utmost importance.…”
Section: Introductionmentioning
confidence: 99%